Avaliação da atividade antiproliferativa in vitro e antitumoral in vivo do composto LQFM030 no tumor ascítico de Ehrlich - Mota, Mariana Flávia da (2013)
Activation of the p53 pathway by inhibition of MDM2 has been proposed as a new strategy for developing new anti-tumor agents. Analogs of cis-imidazoline called nutlins showed ability to block the binding of p53 to MDM2, preventing p53 degradation and thus exhibiting in vivo anti-tumor and in vitro antiproliferative activities. In view of the anti-tumor potential of the nutlins and their complex production, we designed and synthesized analogues as LQFM030 by employing the strategy of molecular simplification. The aim of this study was to evaluate the anti-tumor activity in vivo and the antiproliferative activity in vitro of the LQFM030 compound in the experimental model Ehrlich ascites tumor (EAT). For evaluation of anti-tumor activity in vivo we used male Swiss albino mice that were treated for 10 days with 50, 75 or 150 mg / kg of the compound LQFM030. After treatment, the anti-tumor activity of the compound was assessed by the difference of the weight and ascitic fluid volume, number of tumor cells by trypan blue exclusion test, peritoneal angiogenesis and the VEGF production. The anti-tumor mechanisms were assessed by flow cytometry and we also assessed hematological and biochemical parameters of the animals. The in vitro antiproliferative activity was evaluated in EAT cells by using the trypan blue exclusion method, and the mechanisms involved in the death of EAT cells were investigated by optical and fluorescence microscopy, flow cytometry, real-time PCR and western blot. Data were analyzed by analysis of variance (one-way ANOVA) and subsequent Newman-Keuls test to compare means or by t test using the Graph pad prism program. Means were considered statistically significant when p<0.05. The LQFM030 compound was able to inhibit the tumor of EAT bearing animals in a dose-dependent manner with an ED50 of 150 mg/kg. We also observed reduction in peritoneal angiogenesis and in VEGF production, and the treatment did not significantly change the hematological and biochemical parameters of the animals. The in vitro treatment also showed antiproliferative and cytotoxic concentration-dependent activities, increased the expression of p53 protein and activated the p53 pathway (through activation of proteins p21 and p27 and MDM2 reduction). Furthermore, the compound caused a retention of EAT cells in the G1 phase of the cell cycle and led the cells to apoptosis. We observed apoptosis by the morphology of the cells, DNA fragmentation, externalization of phosphatidylserine and by activation of initiator and effector caspases. The transcription of p53 was not affected by LQFM030, indicating that the regulation of p53 was post-transcriptional. Just as nutlins, LQFM030 showed antitumor activity in vivo and antiproliferative activity in vitro, probably by inhibiting the p53-MDM2 interaction and reactivating p53 and its main functions, the retention in the cell cycle and apoptosis. These results suggest that LQFM030 is an interesting candidate in the development of new anti-tumor therapeutic agents.